Forecasting PT Bank Central Asia Tbk Stock Price Using ARIMA Model - Agna Olivia; Edwin Setiawan Nugraha (Journal of Actuarial, Finance, and Risk Management, 2023)
Stocks are one of the most popular financial market instruments. Issuing shares is one of the company's options when deciding to fund the company. On the other hand, stocks are an investment instrument that many investors choose because stocks are able to provide an attractive level of profit. Autoregressive Integrated Moving Average (ARIMA) model is a method used to predict the stock price of PT Bank Central Asia Tbk. This analysis shows that ARIMA (3,2,0) is the best model for forecasting the stock price of PT. Bank Central Asia Tbk because it has the smallest MAPE among the other model which is 14.03%. This forecasting is very useful for the investor as a guideline in the future for making effective and efficient decisions about stocks on PT Bank Central Asia Tbk.